1982
DOI: 10.1007/bf00491481
|View full text |Cite
|
Sign up to set email alerts
|

?-Adrenoceptor-mediated inhibition of noradrenaline release in rabbit brain cortex slices

Abstract: Brain cortex slices from rabbits were preincubated with [3H]noradrenaline and then superfused and stimulated electrically at 3Hz. In the presence of cocaine 30 microM, unlabelled noradrenaline, alpha-methylnoradrenaline, clonidine, oxymetazoline, xylazine and guanabenz decreased, whereas yohimbine, corynanthine, phentolamine, tolazoline and azapetine increased the stimulation-evoked overflow of tritium. Phenylephrine and prazosin had no effect on the evoked overflow except at concentrations that greatly accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(16 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Studies on presynaptic a-autoreceptors also first indicated heterogeneity within the 2 class (Doxey & Everitt, 1977;Dubocovich, 1979). A species difference between the rabbit and the rat, for example, was a consistent finding (Reichenbacher et al, 1982;Ennis, 1985;Lattimer & Rhodes, 1985;Alabaster et al, 1986;Limberger et al, 1989).…”
Section: Introductionmentioning
confidence: 81%
“…Studies on presynaptic a-autoreceptors also first indicated heterogeneity within the 2 class (Doxey & Everitt, 1977;Dubocovich, 1979). A species difference between the rabbit and the rat, for example, was a consistent finding (Reichenbacher et al, 1982;Ennis, 1985;Lattimer & Rhodes, 1985;Alabaster et al, 1986;Limberger et al, 1989).…”
Section: Introductionmentioning
confidence: 81%
“…Hence, we investigated, whether the phorbol ester-induced PKC activation also impairs directly the M2-autoreceptorcoupled feedback inhibition of noradrenaline release or acts by a different mechanism. Since changes in the concentration of the endogenous ax2-agonist noradrenaline have to be taken into account, when investigating the effects of exogenous agonists or antagonists in the presence of drugs or experimental conditions which strongly affect the concentration of the endogenous agonist (Reichenbacher et al, 1982) (1) At 3 Hz, in the absence of 413-PDB, yohimbine caused a strong enhancement of the evoked noradrenaline release (Figure 4a; note that the increase is expressed as % of the tissue tritium content). The effect of yohimbine was increased in the presence of 413-PDB, reflecting the enhanced autoinhibition due to the higher concentration ofendogenous noradrenaline in the synaptic cleft.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency-dependent modulation of transmitter release by respective agonists and antagonists through activation of presynaptic autoreceptors has also been demonstrated for dopamine and acetylcholine in the rabbit striatum (Cubeddu & Hoffmann, 1983;James & Cubeddu, 1984). Similarly, the effects of a-receptor agonists and antagonists on noradrenaline release from cortical slices (Reichenbacher et al, 1982;Heepe & Starke, 1985) and from sympathetic nerve terminals in the periphery (Limberger & Starke, 1984) largely depend on the parameters of stimulation employed.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists more potently inhibit neurotransmitter release at lower biophase concentrations of transmitter, while antagonists more potently enhance neurotransmitter release the higher the synaptic concentration of transmitter. This has been demonstrated for x2-autoreceptor modulation of noradrenaline release from rabbit ear artery (Limberger & Starke, 1984), rat and rabbit cortical slices (Bauman & Koella, 1980;Reichenbacher et al, 1982;Heepe & Starke, 1985), as well as for D2-and muscarinic autoreceptor modulation ofdopamine and acetylcholine release from rabbit striatum, respectively (Cubeddu & Hoffmann, 1983;James & Cubeddu, 1984).…”
Section: Introductionmentioning
confidence: 89%